2018
DOI: 10.1111/all.13661
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3‐like 1 protein plays a critical role in respiratory syncytial virus‐induced airway inflammation

Abstract: Background: Chitinase 3-like 1 protein (CHI3L1) (YKL-40 in humans and breast regression protein [BRP]-39 in mice) is required for optimal allergen sensitization and Th2 inflammation in various chronic inflammatory diseases including asthma. However, the role of CHI3L1 in airway inflammation induced by respiratory viruses has not been investigated. The aim of this study was to investigate the relationship between CHI3L1 and airway inflammation caused by respiratory syncytial virus (RSV) infection. Methods:We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…Regarding the relationship between CHI3L1 and M2 macrophages, CHI3L1 has been found to stimulate respiratory syncytial virus (RSV)‐induced airway inflammation, partly via M2 macrophage activation . Based on the findings of several in vitro studies, M2 macrophages have recently been subdivided into four subgroups: M2a, M2b, M2c and M2d .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between CHI3L1 and M2 macrophages, CHI3L1 has been found to stimulate respiratory syncytial virus (RSV)‐induced airway inflammation, partly via M2 macrophage activation . Based on the findings of several in vitro studies, M2 macrophages have recently been subdivided into four subgroups: M2a, M2b, M2c and M2d .…”
Section: Discussionmentioning
confidence: 99%
“…Th2 cytokine levels and airway inflammation are known to be elevated in respiratory syncytial virus (RSV) infection but were reportedly diminished in the absence of CHI3L1. 43 In lung metastasis, CHI3L1 also plays a significant role in the pathogenesis of Th2 inflammation. CHI3L1 expression levels were found to be elevated in Th2 cells and CHI3L1-deficient T cells were prone to differentiate into Th1 cells as a result of increased interferon-gamma signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also indicated that CHI3L1 is involved in M2 macrophage polarization in atopic dermatitis and RSV infection. 19 43 This effect could be due to Th2 cytokines, such as IL-4 and IL-13, which are M2 polarization drivers. 45 Therefore, we suspect that increased expression of Th2 cytokines is involved in the development of the M2 phenotype, and that these synergistic effects may promote food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…This usually occurs through mechanisms including upregulation of cell adhesion molecules, pathogen sensing receptors, and Toll-like receptors, which are common immunopathogenic factors mediating or involved in virus-and allergen-induced mucosal inflammation. [84][85][86][87][88][89][90][91] In addition, respiratory viruses were suggested to impact cilia and tight junction integrity in airway epithelial cells through the modulation of ZO-1, claudin-1, and occludin in the airway epithelial barrier, [92][93][94] which may be linked to pathophysiology of airway diseases. The nasal epithelium is the primary portal of entry for respiratory viruses and immediate target for viral replication in the airways.…”
Section: Respiratory Viral Infections and Allergymentioning
confidence: 99%